2015
DOI: 10.1016/j.febslet.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Unusual effects of crowders on heme retention in myoglobin

Abstract: Edited by Stuart FergusonKeywords: Macromolecular crowder Glucose and sucrose Excluded volume effect Heme retention BSA Lysozyme Soft interaction a b s t r a c t Myoglobin (Mb) undergoes pronounced heme loss under denaturing conditions wherein the proximal histidine gets protonated. Our data show that macromolecular crowding agents (both synthetic and protein based) can appreciably influence the extent of heme retention in Mb. Interestingly, glucose and sucrose, the monomeric constituents of dextran and ficoll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…Significant efforts have been devoted to explore the potential effects of macromolecular crowding on protein folding and crowder–protein interactions. Structural and thermodynamic studies of proteins in crowded and confined conditions in vitro have been exploited to describe in vivo protein behavior, which is affected by dominance of various types of interactions occurring in cells. In 2008, Zhou et al presented a thoughtful argument in their review in which polyethylene glycol (PEG) should be avoided as a crowding agent precisely because of its potential for the favorably interaction with the proteins that it is intended to be crowded. As a result, PEG is now fast-becoming something of an exile in the macromolecular crowding community.…”
Section: Introductionmentioning
confidence: 99%
“…Significant efforts have been devoted to explore the potential effects of macromolecular crowding on protein folding and crowder–protein interactions. Structural and thermodynamic studies of proteins in crowded and confined conditions in vitro have been exploited to describe in vivo protein behavior, which is affected by dominance of various types of interactions occurring in cells. In 2008, Zhou et al presented a thoughtful argument in their review in which polyethylene glycol (PEG) should be avoided as a crowding agent precisely because of its potential for the favorably interaction with the proteins that it is intended to be crowded. As a result, PEG is now fast-becoming something of an exile in the macromolecular crowding community.…”
Section: Introductionmentioning
confidence: 99%
“…Since in the case of soft interactions, chemical interactions are happening, it may be suggested that the natures of crowding agents can be a significant factor in the degree of destabilization of proteins. Crowding agents, i.e., low molecular size PEG 400 Da and intermediate sizes (PEG 10 kDa, PEG 8 kDa) [3,57,58], ficoll, dextran [33] and proteins (lysozyme and BSA) [3] also destabilize Mb, and in another report it shows that glucose, an osmolyte, also destabilizes Mb [67]. However, it was reported that glucose and sucrose, the monomeric constituents of dextran-and ficoll-based crowder prevents the heme dissociation at higher concentrations [3].…”
Section: Discussionmentioning
confidence: 99%
“…In myoglobin, porphyrin ring of the heme moiety acts as a chromophore and shows characteristic absorption peak at 409 nm, which originates from the interaction between heme and globin (folded protein) and is a signature of the native myoglobin [1]. Absorption of Mb in the Soret region is extremely sensitive to the milieu of heme and therefore generally has been exploited to monitor disruption in the heme pocket due to change in experimental condition [2,3]. GdmCl-induced denaturation of Mb in the presence of ficoll 70 ( Figure S1A) and dextran 70 ( Figure S1B) was measured in the wavelength range 350-450 nm.…”
Section: Gdmcl-and Urea-induced Mb Denaturation In the Absence And Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies on protein folding in crowded systems with a range of parameters (size, shape, and concentrations) were carried out to understand the phenomenon ( Van Den Berg et al, 1999 ; Van Den Berg et al, 2000 ; Galan et al, 2001 ; Zhou et al, 2004 ; Parray et al, 2019 ; Parray et al, 2020a ; Parray et al, 2020b ; Parray et al, 2020c ; Parray et al, 2020d ; Nasreen et al, 2020 ). Protein folding has been examined in the presence of macromolecular crowders like polyethylene glycols (PEGs), ficolls, dextran, and others under physiological environments ( Sasahara et al, 2003 ; Rawat et al, 2010 ; Qu et al, 2012 ; Zhang et al, 2012 ; Sarkar et al, 2013a ; Kundu et al, 2015 ; Shahid et al, 2015 ; Parray et al, 2017 ; Shahid et al, 2017 ; Nasreen et al, 2018 ; Parray et al, 2019 ; Parray et al, 2020a ; Parray et al, 2020b ; Parray et al, 2020c ; Parray et al, 2020d ; Nasreen et al, 2020 ). It is known that macromolecular crowding in cells has a massive effect on biological activity, but predictive studies are relatively unexplored when it comes to its implications.…”
Section: Introductionmentioning
confidence: 99%